2018
DOI: 10.1093/icesjms/fsy034
|View full text |Cite
|
Sign up to set email alerts
|

Aggregations and associations in deep-sea chondrichthyans

Abstract: Group living has been recorded across a diverse range of chondrichthyans, but due to a variety of factors, any inferences of social associations in deep-sea cartilaginous fishes have yet to be described. Using a companion preference analysis, aggregating behaviour and associations in deep-sea chondrichthyans (four holocephalans, ten elasmobranchs) were evaluated across class and group size from long-term archived fisheries independent research trawl survey datasets. Results indicated that not all selected spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
1
14
1
Order By: Relevance
“…4-6 C but decreases after that (Stefánsdóttir et al, 2010). Fish spe- (Finucci et al 2018). The data indicate the presence of an apparent male aggregation location, but the data are limited and in general, the causes of sexual segregation in chondrichthyans is still not well understood and is probably complex (Sims, 2005, Finucci et al, 2017, Finucci et al 2018.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…4-6 C but decreases after that (Stefánsdóttir et al, 2010). Fish spe- (Finucci et al 2018). The data indicate the presence of an apparent male aggregation location, but the data are limited and in general, the causes of sexual segregation in chondrichthyans is still not well understood and is probably complex (Sims, 2005, Finucci et al, 2017, Finucci et al 2018.…”
mentioning
confidence: 95%
“…One feature of many elasmobranchs is the tendency to form aggregations or social groupings (Jacoby et al, 2011) and it has been shown that segregation by sex and maturity stage is common in deep-sea chondrichthyans (Cotton & Grubbs, 2015). Information on deep-sea chimaeras, in particular, is scarce but sexual segregation has been shown to occur in several species (Finucci et al 2018). The objective of this study was to compile data from long-term survey time series better to understand the distribution patterns and other biology of these two species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Aspects of the life history of this species suggest that mate availability may the limiting factor. A female skewed sex ratio and segregation by both size class and sex (Clerkin, 2017;Finucci, Dunn & Jones, 2018) Etmopterus granulosus, does not exhibit a significant association between female size and litter size. This may be attributed to multiple factors, but could be related to resource availability.…”
Section: Discussionmentioning
confidence: 82%